Advances in Materials and Metallurgy Select Proceedings of ICEMMM 2018 - Lakshminarayanan, A. K.; Idapalapati, Sridhar; Vasudevan, M.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book presents select proceedings of the International Conference on Engineering Materials, Metallurgy and Manufacturing (ICEMMM 2018), and covers topics regarding both the characterization of materials and their applications across engineering domains. It addresses standard materials such as metals, polymers and composites, as well as nano-, bio- and smart materials. In closing, the book explores energy, the environment and green processes as related to materials engineering. Given its content, it will prove valuable to a broad readership of students, researchers, and professionals alike. .
1. Composite Materials -- 2. Nano Materials -- 3. Iron and Steel Materials -- 4. Ceramics -- 5. Metal Alloys -- 6. Polymer Materials -- 7. New Energy Materials -- 8. Environmental Friendly Materials -- 9. Bio-materials -- 10. Smart and Intelligent Materials -- 11. Surface Engineering and Coatings.
Keywords: Materials; Materials -- Analysis; Metals; Building materials; Ceramic materials; Materials Engineering; Characterization and Analytical Technique; Metals and Alloys; Structural Materials; Ceramics